KAJIAN LITERATUR REVIEW: STRATEGI PENGEMBANGAN DAN PELATIHAN SDM BERBASIS KOMPETENSI DALAM MENINGKATKAN KINERJA ORGANISASI - Faaikoh, Aisy; Berliana, Tri Gita; Adzani, Masita; Nensytazamalik, Agies Perimiari; Hakim, Adi Lukman (Media Mahardhika, 2026)
This research focuses on the study of competency-based human resource (HR) development and training strategies, with the primary goal of improving overall organizational performance. The research was conducted using a qualitative descriptive approach based on literature review, where data was collected from various academic references, including national journals, scientific books, and research findings related to HR development. The data analysis process was carried out systematically through the stages of information reduction, data presentation, and conclusion drawing, thus obtaining a comprehensive understanding of the most effective HR development and training practices. The results of the study indicate that competency-based training, whether implemented in the workplace or through external programs, can significantly improve employees' technical skills, knowledge, and professional attitudes. Furthermore, the application of SWOT analysis has proven to be an effective tool in identifying strengths, weaknesses, opportunities, and threats that influence the success of HR development programs. The integration of training and career development has also been shown to strengthen employee motivation, loyalty, and productivity. Based on these findings, it can be concluded that competency-based HR development and training is an important investment strategy for organizations, as it not only creates an adaptive and professional workforce but also increases organizational competitiveness amidst global dynamics and ongoing changes in the business environment.